COVID-19 and human reproduction: A pandemic that packs a serious punch. (2nd January 2021) - Anifandis, George; Tempest, Helen G.; Oliva, Rafael; Swanson, Grace M.; Simopoulou, Mara; Easley, Charles A.; Primig, Michael; Messini, Christina I.; Turek, Paul J.; Sutovsky, Peter; Ory, Steve J.; Krawetz, Stephen A.
ABSTRACT: The COVID-19 pandemic has led to a worldwide health emergency that has impacted 188 countries at last count. The rapid community transmission and relatively high mortality rates with COVID-19 in modern times are relatively unique features of this flu pandemic and have resulted in an unparalleled global health crisis. SARS-CoV-2, being a respiratory virus, mainly affects the lungs, but is capable of infecting other vital organs, such as brain, heart and kidney. Emerging evidence suggests that the virus also targets male and female reproductive organs that express its main receptor ACE2, although it is as yet unclear if this has any implications for human fertility. Furthermore, professional bodies have recommended discontinuing fertility services during the pandemic such that reproductive services have also been affected. Although increased safety measures have helped to mitigate the propagation of COVID-19 in a number of countries, it seems that there is no predictable timeline to containment of the virus, a goal likely to remain elusive until an effective vaccine becomes available  and widely distributed across the globe. In parallel, research on reproduction has been postponed for obvious reasons, while diagnostic tests that detect the virus or antibodies against it are of vital importance to support public health policies, such as social distancing and our obligation to wear masks in public spaces. This review aims to provide an overview of critical research and ethics issues that have been continuously emerging in the field of reproductive medicine as the COVID-19 pandemic tragically unfolds. Abbreviations : ACE2: angiotensin- converting enzyme 2; ART: Assisted reproductive technology; ASRM: American Society for Reproductive Medicine; CCR9: C-C Motif Chemokine Receptor 9; CDC: Centers for Disease Control and Prevention; COVID-19: Coronavirus disease 2019; Ct: Cycle threshold; CXCR6: C-X-C Motif Chemokine Receptor 6; ELISA: enzyme-linked immunosorbent assay; ESHRE: European Society of Human Reproduction and Embryology; ET: Embryo transfer; FSH: Follicle Stimulating Hormone; FFPE: formalin fixed paraffin embedded; FYCO1: FYVE And Coiled-Coil Domain Autophagy Adaptor 1; IFFS: International Federation of Fertility Societies; IUI: Intrauterine insemination; IVF: In vitro fertilization; LH: Luteinizing Hormone; LZTFL1: Leucine Zipper Transcription Factor Like 1; MAR: medically assisted reproduction services; MERS: Middle East Respiratory syndrome; NGS: Next Generation Sequencing; ORF: Open Reading Frame; PPE: personal protective equipment; RE: RNA Element; REDa: RNA Element Discovery algorithm; RT-PCR: Reverse=trascriptase transcriptase-polymerase chain reaction; SARS: Severe acute respiratory syndrome; SARS-CoV-2: Severe Acute Respiratory Syndrome Coronavirus 2; SLC6A20: Solute Carrier Family 6 Member 20; SMS: Single Molecule Sequencing; T: Testosterone; TMPRSS2: transmembrane serine protease 2; WHO: World Health Organization; XCR1: X-C Motif Chemokine Receptor